Pengembangan Kepemimpinan yang Adaptif dan Fleksibel: Meningkatkan Ketahanan Organisasi di Era Transformasi Digital - Efrita Norman; Enah Pahlawati (MES Bogor, 2024)
In an era of rapidly evolving digital transformation, adaptive and flexible leadership development is becoming increasingly crucial to ensure organizational sustainability and resilience. Adaptive leadership allows leaders to face dynamic challenges with innovative strategies, while flexible leadership helps adapt management styles to different situations. This research aims to explore the concept of adaptive and flexible leadership and its strategies to increase organizational resilience in the face of rapid technological and market changes. This research was carried out through an in-depth literature study by analyzing relevant literature from various scientific sources and industry reports. The research approach used was a literature study, where data was collected from books, journal articles, industry reports and other reliable sources. The analysis process involved identifying key themes related to adaptive and flexible leadership and their implications for the organization. This method was chosen to gain a comprehensive understanding of the concepts discussed and their relevance in the context of digital transformation. The research results show that adaptive and flexible leadership has a significant positive impact on organizational resilience. Adaptive leaders are able to navigate change more effectively, manage uncertainty, and encourage innovation. Meanwhile, flexibility in leadership allows for quicker response to market changes and employee needs, which in turn improves overall organizational performance. This study also identified several key strategies for developing adaptive and flexible leadership, including continuous training, organizational learning approaches, and emotional skills development. However, this research also revealed several challenges in developing adaptive and flexible leadership, such as high uncertainty, resistance to change , and resource limitations. However, with the right approach, these challenges can be overcome, and organizations can take advantage of the long-term benefits of adaptive and flexible leadership. This research concludes that to remain competitive and resilient in the era of digital transformation, organizations must invest in the development of adaptive and flexible leadership . It is hoped that these findings can provide guidance for practitioners and academics in designing effective leadership development strategies to face future challenges.